Perspectives of people with HIV/AIDS on psychosocial disorders on motivation and quality of Life - Malakauseya, Maxwell Landri Vers; Kailola, Nathalie Elischeva; Maelissa, Merlin Margareth; Pentury, Rosano Carolina; Nari, Janti Pare; Pattipeilohy, Claudia Igreya; Titaley, Christiana Rialine (Universitas 'Aisyiyah Yogyakarta, 2023)
The cause of death of people with HIV/AIDS (ODHA) is not only caused by immunodeficiency factors but also caused by the influence of stigma or social discrimination received, resulting in psychosocial disorders on motivation and quality of life. This study aims to determine the perspective of PLHIV on psychosocial disorders due to discrimination and stigma received and its impact. This research is a qualitative research with a field research design. Data collection using Focus Group Discussion and in-depth interviews involving 18 informants at Yayasan Pelangi Maluku. The impact of psychosocial disorders is experienced as a decrease in the quality and motivation of life. Decreased quality of life was reported by informants, including poor social relationships, problems accepting HIV status, and anger of PLHIV towards themselves. The decrease in motivation to live with PLHIV is reflected in the unwillingness to seek treatment, suicidal ideation, and the desire to transmit HIV. This study showed the existence of psychosocial disorders with a large impact on the motivation and quality of life of PLHIV. This shows the importance of psychosocial assistance to PLHIV through continuous education for families and communities to reduce stigma and discrimination and its impact on PLHIV.